Acetylbritannilactone attenuates contrast-induced acute kidney injury through its anti-pyroptosis effects. Issue 2 (18th February 2020) - Chen, Fei; Lu, Jingchao; Yang, Xiuchun; Xiao, Bing; Chen, Huiqiang; Pei, Weina; Jin, Yaqiong; Wang, Mengxiao; Li, Yue; Zhang, Jie; Liu, Fan; Gu, Guoqiang; et al.
Abstract: Contrast-induced acute kidney injury (CI-AKI) is a severe complication caused by intravascular applied radial contrast media (CM). Pyroptosis is a lytic type of cell death inherently associated with inflammation response and the secretion of pro-inflammatory cytokines following caspase-1 activation. The aim of the present study was to investigate the protective effects of acetylbritannilactone (ABL) on iopromide (IOP)-induced acute renal failure and reveal the underlying mechanism. In vivo and in vitro, IOP treatment caused renal damage and elevated the caspase-1 (+) propidium iodide (PI) (+) cell count, interleukin (IL)-1β and IL-18 levels, lactate dehydrogenase (LDH) release, and the relative expression of nucleotide-binding domain, leucine-rich repeat containing protein 3 (NLRP3), apoptosis-associated speck-like protein (ASC), and gasdermin D (GSDMD), suggesting that IOP induces AKI via the activation of pyroptosis. Furthermore, the pretreatment of ABL partly mitigated the CI-AKI, development of pyroptosis, and subsequent kidney inflammation. These data revealed that ABL partially prevents renal dysfunction and reduces pyroptosis in CI-AKI, which may provide a therapeutic target for the treatment of CM-induced AKI.